Effect of Topical Application of Controlled Release Bsphosphonate Risedronate to Prevent Relapse after Orthodontics Treatment: A Study In Guinea Pig - Dr.drg. Tita Ratya Utari, Sp.Ort (Asian Pasific orthodontic Society, 2014)
the aim of the study was to investigate the effect of bisphosphonate risedronate with gelatin hydrogel as a carrier to prevent relapse